Hubungan tingkat pengetahuan, sikap dan perilaku terhadap status kebersihan gigi siswa umur 10-12 tahun di SD N 18 Pemecutan - Made Yuni Astari; Putu Lestari Sudirman; Mia Ayustina Prasetya (School of Dentistry Faculty of Medicine Udayana University, 2021)
Background: The mixed dentition phase is the stage to complete the permanent tooth. Besides that some students have crowding tooth in this phase. If the dental hygiene was poor . It will cause caries in some permanent teeth and it cant be replaced like deciduous teeth. The presence of puberty and hormonal change 10-12th years old, increase the sensitivity of gingiva to biofilm and it can cause some problem such as caries, gingivitis and stomatitis. The relationship between knowledge, attitude and behavior greatly affects the improvement of dental and oral health status, so it needs to be investigated. The aim of this study is to investigate the correlations between knowledge, attitude and behavior at the mixed dentition stage (10-12 years old) towards dental hygiene status in SD N 18 Pemecutan Method: The study uses cross sectional analytic observational method. The sample was 108 respondents from 10-12 years old students at SD N 18 Pemecutan. Knowledge, attitude, behaviors data were obtained through questionnaires, and dental hygiene status data was measured by OHIS indeks Result: spearman’s rank bivariable analysis shows that knowledge, attitude, and behavior variable were not related to dental hygiene status (Sig. > 0.01) Conclusions: Good knowledge and attitude do not always have a good score in oral hygiene status but behavior of maintaining good dental hygiene has a direct influence on dental hygiene status. Latar Belakang : Tidak sedikit siswa mengalami gigi berjejal saat memasuki tahap penyempurnaan gigi permanen. Pada fase gigi permanen apabila mengalami karies karena status kebersihan gigi buruk tidak dapat diganti seperti halnya gigi susu. Usia 10-12 tahun siswa memauski masa pubertas dan perubahan hormonal yang dapat meningkatkan kepekaan gingiva terhadap biofilm kemudian menimbulakan masalah seperti karies, gingivitis stomatitis. Hubungan pengetahuan, sikap dan perilaku siswa yang baik berpengaruh terhadap peningkatan status kebersihan dan kesehatan gigi sehingga diperlukan penelitan lebih lanjut. Tujuan dari penelitian ini adalah untuk mengetahui hubungan pengetahuan, sikap dan perilaku siswa fase gigi bercampur (10-12 Tahun) dan status kebersihan gigi di SD N 18 Pemecutan Metode Penelitian: Penelitian menggunakan metode observasional analitik cross sectional. Sampel sebanyak 108 responden siswa 10-12 tahun di SD N 18 Pemecutan. Data pengetahuan, sikap dan perilaku di peroleh melalui kuisioner, dan data status kebersihan gigi diukur dengan indeks OHI-S Hasil: Analisis bivariabel spearman’s rank menghasilkan variabel pengetahuan, sikap dan perilaku yang tidak berhubungan dengan status kebersihan gigi (Sig. > 0.01). Kesimpulan: Pengetahuan dan sikap yang baik belum tentu memiliki nilai status kebersihan gigi yang baik, namun perilaku menjaga kebersihan gigi yang baik mempunyai pengaruh langsung terhadap status kebersihan gigi